What is the expected benefit of patient-centric clinical development in oncology?. Issue 3 (4th May 2022) - Serra, Alessandra; Mozgunov, Pavel; Jaki, Thomas; Rigat, Fabio
ABSTRACT: The identification and quantification of predictive biomarkers characterize personalized medicine approaches and patient-centric clinical development. In practice, the sponsor needs evaluating whether biomarker-informed clinical development strategies are more likely to benefit current and future patients. To this end, a simple metric is proposed and assessed here quantifying the expected clinical benefit (ECB) of clinical development programmes. Using simulation scenarios and endpoints relevant to oncology, the ECB of a simple biomarker-informed strategy is shown to be specific and sensitive. Also, the ECB difference is shown to increase in the biomarker-driven incremental efficacy and with the population prevalence of biomarker-positive study participants.